Towards Sustainable Production: The Case of the Manufacturing Industry in Colombia and México - Hernández González, Mariana; Rodríguez Sánchez, Patricia Jissette (European Journal of Sustainable Development, 2018)
The United Nations’ agenda for sustainable development highlights the need to create resilient infrastructures for a sustainable industry that fosters innovation, while increasing resource utilization at all levels of the supply chain, from production to the final consumer. This research aims to expose the strategies that the manufacturing industry undertook towards sustainable development in Colombia and Mexico between 2010 and 2016, in which the documentary research methodology with a qualitative approach was utilized, supported by specialized academic journals. As a result, the countries’ efforts can be analyzed in 3 categories: the development of new products, the use of new sources of energy such as renewables, and the construction of a green market around one true sustainable production. Keywords: Sustainable production, green market, renewable energy, sustainable development